Sports - Hammond, Tim.; King, Dave (New York : Distributed by Random House, 1988)
Examines the equipment, rules, and background of many different team, target, and court sports, including soccer, rugby, Gaelic football, softball, cricket, ice hockey, table tennis, archery, and pool.
Includes index.
Elem. School Library Collection.
School Library Journal.
Wilson's Junior High School.
7.2
5-8
Keywords: Photography of sports -- Juvenile literature; Sports -- Pictorial works -- Juvenile literature; Sports; Sports